Primitive Reflexes and Dementia in Adults With Down Syndrome. Issue 1 (February 2022) - Harp, Jordan; Koehl, Lisa; Van Pelt, Kathryn; Head, Elizabeth; Jicha, Gregory; Robertson, William; Lightner, Donita; Lott, Ira; Schmitt, Frederick
Abstract : Background and Objectives: To determine whether primitive reflexes serve as an indicator of dementia in adults with Down syndrome (DS), we collected neurologic examination data, cognitive and behavioral assessments, and clinical consensus diagnoses of dementia from 92 adults with DS. Methods: In a cross-sectional, observational study of a regional cohort, χ 2 and Fisher exact tests examined individual reflexes across the diagnostic group (no, possible, or probable dementia). In 64 participants with all 8 reflexes assessed, the number of primitive reflexes was assessed as a predictor of diagnosis using age-controlled multinomial logistic regression and of performance on clinical assessments (Brief Praxis Test [BPT], Severe Impairment Battery [SIB], and the Dementia Questionnaire for People with Learning Disabilities [DLD]) using age-adjusted linear regression. Results: Primitive palmomental, grasp, snout, and suck reflexes were more frequent in individuals with probable dementia, but all participants showed at least 1 primitive reflex. Multiple primitive reflexes in combination served as a better indicator of dementia, with each additional abnormal reflex tripling probability of the probable dementia group membership controlling for age. Abnormal reflex count was not associated with direct assessment of cognition and praxis (SIB and BPT) but associated with informant ratings of cognitive and behavioral functioning (DLD). Discussion: The presence of multiple reflexes serves as an indicator of dementia status in DS as a supplement to direct assessment of cognition and praxis. The reflex examination may serve as a tool in the multimethod evaluation for dementia in DS, as it appears unaffected by intellectual disability and language mastery.